SELF-CONCEPT DISORDER CAUSED BY NEGATIVE STIGMA FROM SOCIETY TOWARDS SOMEONE WHO HAS EXPERIENCED COVID-19 - Gardha Rias Arsy; Sri Hindriyastuti (Nurse and Health: Jurnal Keperawatan, 2022)
Background: A patient who has experienced or has been infected with the corona virus has received various kinds of inappropriate responses from the community, family, and health workers. The emergence of negative stigmas from the community towards COVID-19 patients makes the patient's psychological state disturbed. Objectives: The purpose of this study was exploring the experience of the self-concept of someone who has experienced COVID-19. Methods: Participants in this interpretative phenomenology study were 10 participants who had met the criteria in this study. The research data obtained in the form of statements expressed by the participants are searched for keywords then compiled and grouped based on categories that have the same meaning, then the categories obtained will be arranged to get sub-themes, and for the last one the sub-themes will be compiled again. Become the theme of the research results. The themes that have been obtained in the analysis process will be validated against the initial transcript. If it is appropriate then these themes can be used as answers to research questions. The implementation of this research uses data analysis techniques Interpretative Phenomenology Analysis (IPA) in the analysis process. The participant in this study was someone who had experienced and managed to recover from COVID-19 and had returned to his activities in the community in Gondoharum Village. The selection of participants in this study used a purpose sampling technique according to the criteria that had been selected by the researcher. The criteria that have been set in the study are people who have experienced COVID-19, people who have recovered from COVID-19, Indonesian Citizen, willing to be a participant, and willing to be interviewed and recorded during the research process. Results: This theme provides an overview of the meaning of the feeling of being shunned by participants due to being positive for COVID-19. This theme answers from the lived relationship in phenomenological research. The theme of “Feeling isolated due to negative stigma from society” includes Families keeping their distance when communicating and People are afraid to interact and stay away. Conclusion: The high positive number of COVID-19 in Indonesia has led to the emergence of a negative community stigma towards patients exposed to COVID. Stigma appears in social behavior such as ostracizing patients who have recovered, refusing and ostracizing because they are considered carriers of the virus.